Fixed Prosthodontic Treatment of Patient with Anterior Deep Bite- A case report - Ivony Fitria; Gunawan Gunawan; Qorrie Furqan Al Annuri; Ayesa Rifani (Andalas Dental Journal, 2022)
The condition of oral cavity greatly influences the patient's dental care and treatment. In prosthodontic treatments, the anatomy and arrangement of the teeth is one of the factors that must be considered in order to be able to plan a treatment design. Deep bite with larger overlap of the maxillary and mandibular incisors make the lateral load borne by the teeth become greater. This can cause damage to the tooth and periodontal tissues, as well as failure of the denture. This article reports on the treatment of edentulous of the tooth 21 with deep bite with convetional brigde PFM. Clinical examination showed that there was an overlap between the upper central incisors and the lower incisors by 5 mm and there was a toothwear defect in the form of attrition on teeth 31 and 41. The patient was planned to have a 3 unit conventional bridge made with porcelain fused to metal with a metal backing design to reduce the thickness of the preparation in palatal area and minimize contact with opposing teeth. At the insertion, the patient's occlusion is checked and evaluated so that there are no premature contacts and occlusal interference during centric and eccentric movements. The patient is satisfied with the results of the treatment. Treatment with fixed partial denture in deepbite must be well designed and planned to achieve successful treatment.